2009
DOI: 10.1186/1471-2407-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of expression and CGH arrays pinpoints novel candidate genes in Ewing sarcoma family of tumors

Abstract: BackgroundEwing sarcoma family of tumors (ESFT), characterized by t(11;22)(q24;q12), is one of the most common tumors of bone in children and young adults. In addition to EWS/FLI1 gene fusion, copy number changes are known to be significant for the underlying neoplastic development of ESFT and for patient outcome. Our genome-wide high-resolution analysis aspired to pinpoint genomic regions of highest interest and possible target genes in these areas.MethodsArray comparative genomic hybridization (CGH) and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 52 publications
3
66
0
Order By: Relevance
“…Moreover, there is a substantial disagreement about which particular CNAs are clinically relevant in ES (Kullendorff et al, 1999;Tarkkanen et al, 1999;Brisset et al, 2001;Ozaki et al, 2001;Hattinger et al, 2002), probably because of the small size of the sample series analyzed (Knuutila et al, 1998;Kullendorff et al, 1999;Tarkkanen et al, 1999;Ferreira et al, 2008;Savola et al, 2009) and/or the use of techniques with low resolution/sensitivity (Knuutila et al, 1998;Kullendorff et al, 1999;Tarkkanen et al, 1999;Brisset et al, 2001;Ozaki et al, 2001;Hattinger et al, 2002), as most previous reports relied on karyotyping and/or metaphase CGH.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, there is a substantial disagreement about which particular CNAs are clinically relevant in ES (Kullendorff et al, 1999;Tarkkanen et al, 1999;Brisset et al, 2001;Ozaki et al, 2001;Hattinger et al, 2002), probably because of the small size of the sample series analyzed (Knuutila et al, 1998;Kullendorff et al, 1999;Tarkkanen et al, 1999;Ferreira et al, 2008;Savola et al, 2009) and/or the use of techniques with low resolution/sensitivity (Knuutila et al, 1998;Kullendorff et al, 1999;Tarkkanen et al, 1999;Brisset et al, 2001;Ozaki et al, 2001;Hattinger et al, 2002), as most previous reports relied on karyotyping and/or metaphase CGH.…”
Section: Introductionmentioning
confidence: 93%
“…Likewise, while major efforts in the copy number alteration (CNA) profiling of ES have succeeded in assessing the frequency of recurrent genomic alterations (Knuutila et al, 1998;Kullendorff et al, 1999;Tarkkanen et al, 1999;Brisset et al, 2001;Ozaki et al, 2001;Hattinger et al, 2002;Roberts et al, 2008), few have integrated genomic and transcriptomic profiles and gained in-depth information about their correlation with clinical parameters (Ferreira et al, 2008;Savola et al, 2009). Moreover, there is a substantial disagreement about which particular CNAs are clinically relevant in ES (Kullendorff et al, 1999;Tarkkanen et al, 1999;Brisset et al, 2001;Ozaki et al, 2001;Hattinger et al, 2002), probably because of the small size of the sample series analyzed (Knuutila et al, 1998;Kullendorff et al, 1999;Tarkkanen et al, 1999;Ferreira et al, 2008;Savola et al, 2009) and/or the use of techniques with low resolution/sensitivity (Knuutila et al, 1998;Kullendorff et al, 1999;Tarkkanen et al, 1999;Brisset et al, 2001;Ozaki et al, 2001;Hattinger et al, 2002), as most previous reports relied on karyotyping and/or metaphase CGH.…”
Section: Introductionmentioning
confidence: 99%
“…Of these articles, 60 were excluded based on the titles and abstracts because of obvious lack of relevance, and 89 were excluded because of obvious duplicated publications. The following articles were also excluded: three duplicated publications (Zhou et al, 2007b;Zhou et al, 2010a;Yang et al, 2014); three without data for HR and 95%CI calculations and adequate contact with the investigators could not be established (Natrajan et al, 2006;Mao et al, 2008;Hanada et al, 2013); two with a sample size<50 (Hsu et al, 2012;Tao et al, 2014); two in which HDGF expression was not detected by IHC methods (Savola et al, 2009;Zhang et al, 2010); three uncorrelated. Finally, 26 cohort studies were found eligible for the meta-analysis (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Lin et al, 2012;Han et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Zhang et al, 2014), contai...…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…In recent years, elevated levels of hepatoma-derived growth factor (HDGF) have been observed in a variety of malignancies and high levels of HDGF appears to be associated with increased malignancy across cancers, as witnessed by the correlation with adverse characteristics such as poor patient survival (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Savola et al, 2009;Zhang et al, 2010;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Ye et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Hsu et al, 2012;Lin et al, 2012;Han et al, 2013;Hanada et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Yang et al, 2014;Zhang et al, 2014). As a multifunctional protein Bao et al, 2014) widely expressed by many types of human cells, HDGF is involved in the regulations of a myriad of cancer cell activities during cancer transformation (Yang et al, 2013), apoptosis , angiogenesis (Ren et al, 2009), and metastasis (Chen et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…In sarcoma research, Man et al have reported the first application of array-based comparative genomic hybrid ization (aCGH) in osteosarcoma, which identified distinct amplifications and deletions that represent potential therapeutic targets [15] . Similarly, using aCGH and expression arrays, Savola et al have identified important copy number aberrations (CNAs) in Ewing sarcoma and correlated the number of CNAs in the tumor to patient's survival [16] . The study has detected copy number changes in 87% of the cases, and the most recurrent CNAs are gains at chromosome 1q 2, 8, and 12, and losses at 9p and 16q.…”
Section: Dna Mutation and Copy Number Analysismentioning
confidence: 99%